A user centered design methodology for functional and smart garments - Montagna, Gianni (2011)
Bioswim® is a multidisciplinary project that is developing a wireless full-body monitored swimsuit with the aim of increasing swimmer performance. The different points of view of the multiple working groups brought to the project a different vision that expanded the primary aim of the project to a universal level where the application of the instrumented suit for other objectives could be a real fact. Given that most research user-centred methodologies, although straying from the user needs, are in the end actually focused on the final design product, a different approach to the problem had to be found by the working group: to have the user’s input as a significant and central part of the project. Within the project, a new methodology - the User Centered Layered Methodology (UCLM), was designed, implemented and tested.